O consumo do futebol e o envolvimento do torcedor em diferentes ambientes com os principais times de Campinas-SP - Costa Junior, Dirceu (2015)
The sports fans are a group of consumers that grows along with the sports industry in Brazil and worldwide. These fans can be classified in several ways based on several factors. Some of these classifications bring this consumer relationship with the involvement of the product. Soccer fans can consume his team???s matches mainly in three environments: in the stadium, at home or in pubs. Therefore, the aim of this study is to understand the relationship between the level of involvement of soccer fans when consumed in different environments. For this research, we conducted semi-structured interviews with Ponte Preta and Guarani fans. The interviews were analyzed by content analysis technique and did not suggest a difference between the degree of involvement and the consumption environment, with fans more or less independent involvement of local consumption, but between the type of involvement and local football consumption. All respondents fans had high cognitive engagement with their teams, but only the fans who attend stadiums exhibited emotional involvement.